Laparoscopic appendicectomy in obese is associated with improvements in clinical outcome: Systematic review. (January 2015) - Dasari, Bobby V.M.; Baker, Jill; Markar, Sheraz; Gardiner, Keith
Abstract: Background : Obese patients with general surgical emergencies provide unique challenges to the emergency surgical teams. Acute appendicitis is the most common adult acute surgical emergency encountered in practice. This systematic review evaluates the role of laparoscopic appendicectomy in obese by comparing the outcomes of laparoscopic appendicectomy in obese versus non-obese and the laparoscopic versus open appendicectomy in obese patients.Methods : Relevant comparative studies were identified from the Cochrane Central Register of Controlled Trials, MEDLINE, Embase and PubMed (1990–2013). Primary outcomes evaluated were mortality, overall morbidity and duration of surgery. Secondary outcomes evaluated were superficial (superficial wound infection) and deep surgical site infection (intra-abdominal abscesses), conversion to open surgery, and cost of the procedure.Results : Seven retrospective cohort studies and one prospective randomized controlled trial met the inclusion criteria. There was no statistically significant difference in the primary and secondary outcomes between the obese and non-obese patients undergoing laparoscopic appendicectomy. Laparoscopic appendicectomy in obese patients is associated with reduced mortality (risk ratio [RR]: 0.19 (95% CI 0.12–0.30), reduced overall morbidity (RR: 0.49 (95% CI: 0.47–0.51)), reduced superficial wound infections (RR: 0.27 (95% CI 0.21–0.35)), shorter operating times and post-operative length of hospital stay, compared to open appendicectomy. Methodological quality of the included studies is low.Conclusion : Laparoscopic appendicectomy appears to be a safer alternative approach to open surgery in obese adult patents. There is no significant difference in the outcomes between the obese and non-obese patients undergoing laparoscopic appendicectomy. Highlights: There is no difference in the outcomes between the obese and non-obese patients undergoing laparoscopic appendicectomy (LA). LA in obese patients is associated with significantly reduced mortality, shorter operating times and reduced length of stay. LA appears to be a safer alternative to open surgery in obese adult patients.